2020
DOI: 10.1371/journal.pone.0230382
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, treatment, costs, and long-term outcomes of patients with fireworks-related injuries (ROCKET); a multicenter prospective observational case series

Abstract: ObjectivePeople in the Netherlands are legally allowed to celebrate New Year's Eve with consumer fireworks. The aim of this study was to provide detailed information about the patient and injury characteristics, medical and societal costs, and clinical and functional outcome in patients with injuries resulting from this tradition. MethodsA multicenter, prospective, observational case series performed in the Southwest Netherlands trauma region, which reflects 15% of the country and includes a level I trauma cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 17 publications
3
18
0
4
Order By: Relevance
“…Whether this impairment also results into a functional impairment has not been investigated extensively. Previous research found limited reduced quality of life and functional outcome 1 year after trauma the reported [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether this impairment also results into a functional impairment has not been investigated extensively. Previous research found limited reduced quality of life and functional outcome 1 year after trauma the reported [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide fireworks are used to invigorate joyful events, such as New Year's Eve. However, despite their spectacular visible and audible effects, they can cause severe injuries, such as burns, eye injuries, and amputations [1][2][3]. These injuries can have devastating effects, with lifelong consequences as a result.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Auf der ganzen Welt werden Feuerwerkskörper eingesetzt, um der Freude über frohe Ereignisse, wie etwa Silvester, Ausdruck zu verleihen. Sie können jedoch trotz ihrer spektakulären visuellen und akustischen Effekte schwere Verletzungen wie Verbrennungen, Augenverletzungen und Amputationen verursachen [1-3]. Derartige Verletzungen können verheerende Auswirkungen und lebenslange Schäden zur Folge haben.…”
Section: Introductionunclassified
“…Seit 2012 ist diese Zahl auf etwa 400 Patienten in 2019–2020 zurückgegangen [4]. Meist handelte es sich um junge Männer vor allem mit Verbrennungen der oberen Extremitäten oder Augenverletzungen [1, 3, 5-7].…”
Section: Introductionunclassified